NUTRITIONAL STATUS ASSESSMENT OF FEMALE CANCER PATIENTS IN COCHIN, KERALA - RASHMI H. POOJARA*; ANOL THOMAS (The Journal of Research ANGRAU, 2021)
The study envisaged the assessment of nutritional, functional status and, Quality of Life (QoL) among selected female cancer patients undergoing cancer therapy. The findings suggested that breast cancer was the leading type of cancer and the majority of the patients were in the terminal stages of cancer. The Subjective Global Assessment (SGA) revealed that the majority of subjects belonged to the mildly-moderately nourished category. All the study subjects had an inadequate nutrient intake concerning energy, protein, fat, calcium, iron, and ascorbic acid. A statistically significant difference was evident between the actual and suggested nutrient intake. The mean values of physical, social/family, emotional and functional well-being using the FACT-G scale were computed to be 16.6, 18.8, 11.2, and 10.8, respectively showing that QoL was poor among study subjects, thus, impacting cancer therapy. The nutrient intake of the patients was compared with SGA grading and it was found that there was a statistically significant difference in the nutrient intake among the patients belonging to different nutritional status categories with the lowest intake in the severely malnourished